An ABS consumable for FDM rapid unpacking 3D printing and a preparation method and application thereof
Patent Information
- Application Number
- CN202611155625.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-10-27
AI Technical Summary
[0006]然而,注塑成型与FDM 3D开箱打印在成型原理上存在本质差异,注塑成型是熔体在模具型腔中一次填充成型,整体在模具的约束下同时冷却固化,温度场和应力场相对均匀;FDM 3D开箱打印是熔体逐层堆积,每层在不同时间、不同温度下单独冷却固化,温度场和应力场呈现高度非均匀的时空分布特征,且打印环境为无预热腔、无封闭打印舱
本发明的ABS耗材可在无封闭打印舱、无预热腔的开放式FDM打印机上以200~400mm/s的高速进行打印,突破了常规ABS耗材“必须封箱打印、打印速度慢(50~200mm/s)”的技术瓶颈,显著提高了打印效率和使用便捷性,可适用于各种类型的FDM打印机,包括开放式、半开放式和封闭式设备,使用场景大幅拓宽;
Abstract
Description
Technical Field
[0001] This invention relates to the field of 3D printing consumables technology, and in particular to an ABS consumable for FDM rapid unpacking 3D printing, its preparation method and application. Background Technology
[0002] Acrylonitrile-butadiene-styrene copolymer (ABS) is one of the most commonly used engineering plastics in FDM printing. It boasts excellent mechanical properties, good heat resistance, and high surface quality, making it widely used in consumer-grade 3D printing, education, design verification, and prototype fabrication. However, ABS currently faces two main problems in FDM printing, affecting its application scope and ease of use.
[0003] Firstly, the recommended printing speed for ABS consumables is currently typically 50-200 mm / s, which is inefficient and fails to meet the demands of industrial production. As the printing speed increases, the residence time of the melt in the nozzle shortens, resulting in insufficient plasticization. Simultaneously, the extrusion rate increases dramatically, causing drastic changes in the tensile rheological behavior of the melt during printing, which can easily lead to poor interlayer adhesion and surface defects.
[0004] Secondly, currently, ABS materials must be printed in a closed-system printing environment during FDM printing. This is because, during the printing process, molten ABS (approximately 220-270℃) rapidly cools to room temperature after being extruded from the nozzle, resulting in a temperature difference of over 200℃ and generating significant internal stress. Furthermore, since FDM is a layer-by-layer process, each layer solidifies at different times and temperatures, leading to uneven stress distribution and making the printed parts prone to defects such as warping, cracking, and interlayer delamination. Therefore, to address the warping issue, ABS materials require enclosed printing, allowing the printed parts to cool slowly in a uniform thermal environment. However, closed-system printing equipment is costly, bulky, and makes it difficult to observe the printing process, limiting the applicability and ease of use of ABS consumables. In recent years, a large number of open or semi-open FDM printers (without a closed chamber or preheating cavity) have emerged on the market. These devices cannot provide a sealed, insulated environment, making the warping problem particularly prominent when printing with conventional ABS consumables.
[0005] In addition, in the field of injection molding, there is a technical inspiration to use hollow glass microspheres to reduce the warpage of PC / ABS alloy materials. For example, Chinese patent CN202510746922.5 discloses a low-density, low-warpage PC / ABS alloy material for electronic and electrical appliances. It uses KH-550 silane coupling agent to modify the surface of thin-walled hollow glass microspheres (modification temperature 110-130℃, 15-30min), and combines it with modified special whisker reinforcement filler for injection molding of electronic and electrical components, achieving the technical effect of low warpage.
[0006] However, injection molding and FDM 3D open-box printing differ fundamentally in their molding principles. Injection molding involves the molten material filling a mold cavity in a single pass, with the entire material simultaneously cooling and solidifying under the mold's constraints, resulting in a relatively uniform temperature and stress field. In contrast, FDM 3D open-box printing involves the molten material being deposited layer by layer, with each layer cooling and solidifying separately at different times and temperatures. This results in a highly non-uniform spatiotemporal distribution of temperature and stress fields, and the printing environment lacks a preheating chamber and a closed printing chamber. This means that "low warp" material formulations used in injection molding cannot be directly and simply transferred to FDM 3D printing. The dimensional stability and cooling uniformity provided by the mold constraints in injection molding are completely absent in the open environment of FDM 3D printing. Directly applying low warp formulations used in injection molding to FDM printing not only fails to achieve high-speed printing but also makes it difficult to guarantee even basic interlayer bonding and molding.
[0007] Therefore, developing an ABS consumable specifically designed for the characteristics of FDM 3D printing, capable of high-speed printing without the need for box sealing, and exhibiting low warpage, has significant technological value and market implications. Summary of the Invention
[0008] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide an ABS consumable for FDM rapid unpacking 3D printing, its preparation method and application. Modified hollow glass microspheres and antioxidants are compounded and act synergistically on the ABS matrix to develop an ABS consumable specifically designed for the characteristics of FDM 3D printing process, which is printable from the box and has low warpage.
[0009] To achieve the above objectives, the technical solution adopted by the present invention is as follows: An ABS filament for FDM (Flash Deposition Model) quick-out 3D printing, comprising, by weight percentage: ABS matrix 65.0-75.0 wt%; Elastomer 10.0-15.0 wt%; Bifunctional composite filler 3.0-8.0 wt%; Plasticizer 2.0-5.0 wt%; The bifunctional composite filler is a mixture of modified hollow glass microspheres and antioxidants.
[0010] The modified hollow glass microspheres are materials modified with KH-550 silane coupling agent. The specific process involves placing 2.5 wt% KH-550 silane coupling agent and hollow glass microspheres in a solvent system with an ethanol / water volume ratio of 9:1 and reacting at 80°C for 2 hours to obtain the modified hollow glass microspheres (X-ray photoelectron spectroscopy (XPS) showed a surface grafting rate of 91.3% and an interfacial binding energy of 2.95 J / m²). Unmodified hollow glass microspheres contain a large number of hydroxyl groups on their surface, exhibiting hydrophilicity and poor interfacial compatibility with the hydrophobic ABS matrix. Direct blending easily leads to agglomeration and interfacial debonding, thus reducing material performance. After modification, the amino groups on KH-550 form hydrogen bonds or covalent bonds with the polar groups in the ABS molecular chain, thereby establishing chemical bonds and interfacial compatibility between the hollow glass microspheres and the ABS matrix.
[0011] The antioxidants are hindered phenolic antioxidant 1010 (which terminates the oxidation chain reaction by capturing peroxide free radicals) and phosphite antioxidant 168 (which exerts an auxiliary antioxidant effect by decomposing hydrogen peroxides). The combination of the two produces a synergistic antioxidant effect.
[0012] The modified hollow glass microspheres, hindered phenolic antioxidant 1010, and phosphite antioxidant 168 are mixed in a mass ratio of 100:3:2. The synergistic effect of the bifunctional composite filler stems from the low coefficient of thermal expansion of the modified hollow glass microspheres (≈4×10). -6 The physical-chemical coupling of the modified hollow glass microspheres with the endothermic thermal decomposition properties of the antioxidants: the modified hollow glass microspheres slow down the local shrinkage rate during the cooling stage, while the antioxidants inhibit free radical chain degradation. Together, they mitigate the spatiotemporal asynchrony between the temperature field and the stress field. Furthermore, the bifunctional composite filler does not require the synthesis of new compounds; performance improvements can be achieved solely through physical compounding and controllable surface treatment. The process is simple, cost-effective, and easily scaled up for industrial application.
[0013] The elastomer is a styrene-butadiene block elastomer or a thermoplastic polyurethane elastomer, used to improve the toughness and impact resistance of the ABS matrix. At the same time, the low glass transition temperature of the elastomer keeps it in a highly elastic state at room temperature, which can absorb some of the thermal shrinkage stress through chain segment movement, thereby absorbing thermal stress and alleviating warping to a certain extent.
[0014] The plasticizer is tributyl acetyl citrate (ATBC), which is used to improve the processing flowability and flexibility of the consumable. By inserting itself between the molecular chains of the ABS matrix, it weakens the intermolecular forces, increases the chain segment mobility, thereby reducing melt viscosity and improving processing flowability.
[0015] A method for preparing ABS consumables for FDM rapid unpacking 3D printing as described above includes the following steps: S1: The modified hollow glass microspheres are blended with an antioxidant to obtain a bifunctional composite filler, which is then mixed evenly with the ABS matrix, elastomer, and plasticizer in the specified proportions to obtain a blend.
[0016] S2: The blend is melt-blended, extruded, and granulated using a twin-screw extruder to obtain granules.
[0017] S3: The extruded granules are melted, extruded, drawn, and cooled using a single-screw extruder to obtain ABS consumable wire.
[0018] In step S2, the extrusion temperature of the twin-screw extruder is 180-220℃, the die temperature is 220℃, and the length-to-diameter ratio is 30-40:1; in step S3, the extrusion temperature of the single-screw extruder is 180℃-220℃, the die temperature is 220℃, and the length-to-diameter ratio is 40-50:1.
[0019] An application of the ABS consumables for FDM rapid unpacking 3D printing as described above involves printing the ABS consumables on an open 3D printing device without a preheating chamber or a closed printing chamber, under conditions of a nozzle temperature of 270±2℃, a heated bed temperature of 90±1℃, and a printing speed of 200-400mm / s.
[0020] The beneficial effects of this invention are: The ABS consumables of this invention can be printed at a high speed of 200~400mm / s on open FDM printers without a closed printing chamber or a preheating cavity. This breaks through the technical bottleneck of conventional ABS consumables, which "must be printed in a sealed box and have a slow printing speed (50~200mm / s)". It significantly improves printing efficiency and ease of use and is applicable to various types of FDM printers, including open, semi-open and closed equipment, greatly expanding the application scenarios. This invention utilizes the synergistic effect of the physical buffering (low coefficient of thermal expansion + hollow structure absorbing thermal stress) of modified hollow glass microspheres and the chemical inhibition (inhibition of thermal oxidative degradation) of antioxidants. Under high-speed open-box printing conditions of 400mm / s, the warpage height of a standard 200×200×50mm print is ≤0.14mm, demonstrating superior consumable performance. Compared with existing low-warpage materials for injection molding, this invention does not simply transfer the injection molding formula to 3D printing. Instead, it systematically redesigns the ABS consumables to meet the low-warpage requirements and achieve a high-speed open-box printing speed of 400mm / s, a technical effect that cannot be achieved in conventional ABS and existing injection molding formulas. Detailed Implementation
[0021] In the following examples, all materials used are commercially available products. Example
[0022] An ABS filament for FDM (Flash Deposition Model) quick-out 3D printing, comprising, by weight percentage: ABS matrix 74.7wt% (LG HW265, Mw=2.1×10⁻⁶) 5 ), 15.0 wt% styrene-butadiene block elastomer (Kraton G1657), 5.0 wt% bifunctional composite filler (modified hollow glass microspheres, hindered phenolic antioxidant 1010 and phosphite antioxidant 168 compounded in a mass ratio of 100:3:2), 4.5 wt% ATBC plasticizer, with the balance being 0.5 wt% calcium stearate lubricant and 0.3 wt% antioxidant synergist (Irganox 1076).
[0023] The modified hollow glass microspheres are materials modified with KH-550 silane coupling agent. The specific process is as follows: 2.5 wt% KH-550 silane coupling agent and hollow glass microspheres are placed in a solvent system with an ethanol / water volume ratio of 9:1 and reacted at 80℃ for 2 hours to obtain the modified hollow glass microspheres. The particle size distribution D of the modified hollow glass microspheres was measured. 50 =38.2±1.6μm, wall thickness 1.2±0.1μm, and surface amino density reaches 0.87mmol / g after silane coupling modification.
[0024] A method for preparing ABS consumables for FDM rapid unpacking 3D printing as described above includes the following steps: S1: The modified hollow glass microspheres are blended with an antioxidant to obtain a bifunctional composite filler, which is then mixed with the ABS matrix, elastomer, and plasticizer in a specified ratio to obtain a blend. S2: The blend is melt-blended, extruded, and granulated using a twin-screw extruder. The extrusion temperature is 200°C, the die temperature is 220°C, and the length-to-diameter ratio is 35:1 to obtain granules, which are then vacuum-dried at 80°C for 4 hours. S3: The extruded granules are melt-extruded using a single-screw extruder (extrusion temperature is 200℃, die temperature is 220℃, length-to-diameter ratio is 45:1), drawn into wire, and cooled to obtain ABS consumable wire.
[0025] An application of the aforementioned ABS filament for rapid unpacking 3D printing using FDM is described. The ABS filament is printed on an open 3D printer (Nozle Ø0.4mm, layer thickness 0.2mm) without a preheating chamber or enclosed printing bay, under conditions of nozzle temperature 270℃, heated bed temperature 90℃, and printing speed 400mm / s. After printing a standard 200×200×50mm part, testing was conducted. The measured first-layer adhesion was ≥2.8MPa, with no first-layer peeling or edge lifting observed after 50 consecutive prints. The warpage height at 400mm / s high speed was measured to be 0.1mm (n=5, RSD=3.2%), and the unpacking printing success rate was 100%. Example
[0026] An ABS filament for FDM (Flash Deposition Model) quick-out 3D printing, comprising, by weight percentage: The composition includes 73.7 wt% ABS matrix, 15.0 wt% styrene-butadiene block elastomer, 6.0 wt% bifunctional composite filler (modified hollow glass microspheres, hindered phenolic antioxidant 1010 and phosphite antioxidant 168 in a mass ratio of 100:3:2), 4.5 wt% ATBC plasticizer, and the balance being 0.5 wt% calcium stearate lubricant and 0.3 wt% antioxidant synergist (Irganox 1076).
[0027] An application of the ABS filament for FDM rapid unpacking 3D printing as described above involves printing the ABS filament on an open 3D printing device (Nozle Ø0.4mm, layer thickness 0.2mm) without a preheating chamber or a closed printing chamber, under the conditions of a nozzle temperature of 265-275℃ (increasing from bottom to top for three layers), a heated bed temperature of 95℃, and a printing speed of 400mm / s. The printing process resulted in 50 consecutive prints without any first-layer peeling or edge curling, achieving a 100% unpacking success rate.
[0028] The remaining preparation methods, printing methods, and parameters are the same as in Example 1. Example
[0029] An ABS filament for FDM (Flash Deposition Model) quick-out 3D printing, comprising, by weight percentage: The composition includes 76.1 wt% ABS matrix, 15.0 wt% styrene-butadiene block elastomer, 3.6 wt% bifunctional composite filler (modified hollow glass microspheres, hindered phenolic antioxidant 1010 and phosphite antioxidant 168 in a mass ratio of 100:3:2), 4.5 wt% ATBC plasticizer, and the balance being 0.5 wt% calcium stearate lubricant and 0.3 wt% antioxidant synergist (Irganox 1076).
[0030] The remaining preparation methods, printing methods, and parameters are the same as in Example 1. Example
[0031] An ABS filament for FDM (Flash Deposition Model) quick-out 3D printing, comprising, by weight percentage: The composition includes 71.7 wt% ABS matrix, 15.0 wt% styrene-butadiene block elastomer, 8.0 wt% bifunctional composite filler (modified hollow glass microspheres, hindered phenolic antioxidant 1010 and phosphite antioxidant 168 in a mass ratio of 100:3:2), 4.5 wt% ATBC plasticizer, and the balance being 0.5 wt% calcium stearate lubricant and 0.3 wt% antioxidant synergist (Irganox 1076).
[0032] The remaining preparation methods, printing methods, and parameters are the same as in Example 1.
[0033] Comparative Experiment 1: The composition by weight percentage includes: 74.7 wt% ABS matrix, 15.0 wt% styrene-butadiene block elastomer, 5.0 wt% bifunctional composite filler (hollow glass microspheres without KH-550 modification, hindered phenolic antioxidant 1010 and phosphite antioxidant 168 compounded in a mass ratio of 100:3:2), 4.5 wt% ATBC plasticizer, and the balance being 0.5 wt% calcium stearate lubricant and 0.3 wt% antioxidant synergist (Irganox 1076). The printing speed was 250 mm / s. The measured warpage height of the finished product was 0.48±0.06 mm (n=5, RSD=5.2%), which was 112.7% higher than that of Example 1 (p<0.01). The first layer adhesion was only 1.82±0.04 MPa (RSD=4.8%), T5% decreased to 326.3±1.5℃, and HDT@0.45MPa was 92±1℃. SEM-EDS showed that the microbead aggregation rate was as high as 18.7±1.3%, and the extrusion line diameter RSD=12.6%.
[0034] Comparative Experiment 2: The composition by weight percentage included: 79.0 wt% ABS matrix, 15.0 wt% styrene-butadiene block elastomer, 0.7 wt% antioxidant, 4.5 wt% ATBC plasticizer, and the balance being 0.5 wt% calcium stearate lubricant and 0.3 wt% antioxidant synergist (Irganox 1076). The printing speed was 250 mm / s. The measured warpage height of the finished product was 0.92 ± 0.08 mm (n=5, RSD=6.1%), which was 327.3% higher than that of Example 1 (p<0.001). The first-layer adhesion was only 1.21 ± 0.03 MPa (RSD=5.3%), T5% was 322.5 ± 1.2℃, and HDT@0.45MPa was 86 ± 1℃. SEM-EDS confirmed that the interfacial phase of the microsphere-free system was missing, and the mismatch of the coefficient of thermal expansion was aggravated (α∥ / α⊥=3.8).
[0035] The remaining preparation methods and parameters of the above comparative experiments are the same as those in Example 1.
[0036] The following is a comparative table of the tests conducted on the ABS consumable wires prepared in Examples 1-4 and Comparative Experiments 1-2: Example 1 400 270 0.1 2.8 2.3 8.3 Example 2 400 270 0.13 2.75 2.4 8.2 Example 3 400 270 0.12 2.82 2.3 8.3 Example 4 400 270 0.14 2.75 3.2 8.1 Comparative Experiment 1 250 270 0.48 1.82 18.7 2 Comparative Experiment 2 250 270 0.92 1.21 / Interface missing It can be seen from the above table: Example Analysis: Considering the performance indicators of Examples 1-4, Example 1 exhibits the best overall performance. Under 400mm / s open-pack printing conditions, this scheme achieves a warpage height ≤0.1mm, demonstrating optimal overall performance and a 100% open-pack printing success rate. Furthermore, in Example 4, when the bifunctional composite filler content reached 8.0wt%, although the warpage height remained at a certain level, the first-layer adhesion began to decrease. Therefore, the amount of bifunctional composite filler added in Example 4 represents the critical addition amount.
[0037] Comparative Experiment Analysis: Comparative Experiment 1 used unmodified hollow glass microspheres, which had extremely poor interfacial compatibility with the ABS matrix. The interfacial phase thickness was 2nm, and there was almost no chemical bonding or physical entanglement between the microspheres and the matrix. During the blending and printing process, severe agglomeration occurred, with an agglomeration rate as high as 18.7%. It was impossible to form a uniformly dispersed stress buffer network in the matrix. This would cause the "rigid cavity buffer" function of the hollow glass microspheres to be completely ineffective, and the anisotropy of thermal shrinkage of the material during the cooling process would be aggravated. Therefore, modification with KH-550 silane coupling agent is a prerequisite for activating the physical buffering and interfacial anchoring functions of the hollow glass microspheres. In Comparative Experiment 2, which did not contain hollow glass microspheres, printing was performed at a speed of only 250 mm / s under open-pack printing conditions. The warpage height of the finished product reached 0.92 mm. This indicates that SEM-EDS confirmed the absence of the interfacial phase in the microsphere-free system, which exacerbated the mismatch in thermal expansion coefficients (α∥ / α⊥=3.8) and exhibited anisotropy. This suggests that the thermal shrinkage stress varies greatly in different directions of the finished product, resulting in severe warpage and causing residual stress to concentrate in the matrix-platform contact area. The melt fracture phenomenon was significant (extrusion wire diameter RSD=16.4%), confirming that the hollow glass microspheres are not merely physically filling the surface, but also reconstruct the heat conduction path and stress dissipation channel through the "microsphere-matrix" gradient modulus transition layer. Their dual-function synergistic effect cannot be simply equated to a weight reduction or dilution effect.
[0038] Warpage Analysis: KH-550 silane-coupled modified hollow glass microspheres maintained a warpage height of <0.14 mm even under high-speed FDM printing at 400 mm / s. Its thermo-mechanical coupling stability stems from the reconstruction of the interfacial stress gradient induced by surface chemical bonding, rather than a simple physical filling effect. When the printing speed jumps to 400 mm / s, traditional materials warp uncontrollably due to thermal conduction lag and imbalance of melt elastic energy storage. However, the "rigid-tough-conductive" triple transition layer constructed by the modified hollow glass microspheres simultaneously delays the accumulation of thermal stress, accelerates energy dissipation, and balances anisotropic expansion, reducing the residual stress peak by 62.3% and increasing the first-layer adhesion to 2.87 MPa.
Claims
1. An ABS consumable for FDM rapid unpacking 3D printing, characterized in that... Included by weight percentage: ABS matrix 65.0-75.0 wt%; Elastomer 10.0-15.0 wt%; Bifunctional composite filler 3.0-8.0 wt%; Plasticizer 2.0-5.0 wt%; The bifunctional composite filler is a mixture of modified hollow glass microspheres and antioxidants.
2. The ABS consumable for FDM rapid unpacking 3D printing according to claim 1, characterized in that: The modified hollow glass microspheres are materials modified with KH-550 silane coupling agent.
3. The ABS consumable for FDM rapid unpacking 3D printing according to claim 1, characterized in that: The antioxidants are hindered phenolic antioxidant 1010 and phosphite antioxidant 168.
4. The ABS consumable for FDM rapid unpacking 3D printing according to claim 3, characterized in that: The modified hollow glass microspheres, hindered phenolic antioxidant 1010, and phosphite antioxidant 168 are mixed in a mass ratio of 100:3:
2.
5. The ABS consumable for FDM rapid unpacking 3D printing according to claim 1, characterized in that: The elastomer is a styrene-butadiene block elastomer or a thermoplastic polyurethane elastomer.
6. The ABS consumable for FDM rapid unpacking 3D printing according to claim 1, characterized in that: The plasticizer is tributyl acetyl citrate.
7. A method for preparing ABS consumables for FDM rapid unpacking 3D printing as described in any one of claims 1-6, characterized in that, Includes the following steps: S1: The modified hollow glass microspheres are blended with an antioxidant to obtain a bifunctional composite filler, which is then mixed with the ABS matrix, elastomer, and plasticizer in a specified ratio to obtain a blend. S2: The blend is melt-blended, extruded, and granulated using a twin-screw extruder to obtain granules; S3: The extruded granules are melted, extruded, drawn, and cooled using a single-screw extruder to obtain ABS consumable wire.
8. The method for preparing ABS consumables for FDM rapid unpacking 3D printing according to claim 7, characterized in that: In step S2, the extrusion temperature of the twin-screw extruder is 180-220℃, the die temperature is 220℃, and the length-to-diameter ratio is 30-40:1; in step S3, the extrusion temperature of the single-screw extruder is 180℃-220℃, the die temperature is 220℃, and the length-to-diameter ratio is 40-50:
1.
9. An application of the ABS consumable for FDM rapid unpacking 3D printing as described in any one of claims 1-6, characterized in that... The ABS consumables were printed on an open 3D printing machine without a preheating chamber or a closed printing chamber, under the conditions of a nozzle temperature of 270±2℃, a heated bed temperature of 90±1℃, and a printing speed of 200-400mm / s.
Citation Information
Patent Citations
Low-density low-warpage PC / ABS alloy material for electronic appliances and preparation method thereof
CN120424488A